Online Based Learning Management System (LMS) on Student Academic Performance - Firman Firman; Muh Arief Muhsin; Goestina Goestina (STAI Hubbulwathan Duri, 2021)
The study aims to analyze students' academic performance using a learning management system (LMS) through the Moodle feature serving as an online-based learning resource, which aims to build an interactive learning process between teachers and students. Implementation of LMS able to save time, material organization and conduct effectively and efficiently. The design of this research is qualitative. It describes the data that has been obtained from the field and the literature related to the discussion of the use of online academic-based learning management systems (LMS). The learning process by utilizing information and communication technology has been used with effective learning. It can be stated that the use of e-learning in LMS has functioned as a learning resource, a learning tool, and a learning system itself. The quality is mainly emphasized in the process, namely the active role of students in learning activities, changing conventional learning patterns of students only accepting existing information (transfer of knowledge) and active patterns.